2020
DOI: 10.1097/gox.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Inequitable Access to Rapid Burn and Reconstructive Care through Geospatial Mapping

Abstract: Summary: Time-critical pathologies, such as the care of burn-injured patients, rely on accurate travel time data to plan high-quality service provision. Geospatial modeling, using data from the Malaria Atlas Project, together with census data, permits quantification of the huge global discrepancies in temporal access to burn care between high-income and low-resource settings. In this study, focusing on the United Kingdom and Ghana, we found that a 3-fold population difference exists with, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…18,19 There is extensive literature suggesting that an overall lack of resources, specialized staff, infrastructure, and technical support in health care facilities results in limited capacity to systematically deliver treatment for burn injuries in LMICs. 2,11,13,[17][18][19]21 For example, Lo et al 22 demonstrated that compared with the United Kingdom, Ghana has a three-fold population difference in access to specialist burn care within an hour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 There is extensive literature suggesting that an overall lack of resources, specialized staff, infrastructure, and technical support in health care facilities results in limited capacity to systematically deliver treatment for burn injuries in LMICs. 2,11,13,[17][18][19]21 For example, Lo et al 22 demonstrated that compared with the United Kingdom, Ghana has a three-fold population difference in access to specialist burn care within an hour.…”
Section: Discussionmentioning
confidence: 99%
“…This can help decentralize care and provide easier access to subspecialty treatment provision. 22,28 Each of these solutions must be considered within the context of specific cultural norms, existing resources, and algorithms of care unique to each environment in LMICs and HICs alike. Although we study epidemiologic trends on a macrolevel, region-specific data are also important.…”
Section: Discussionmentioning
confidence: 99%
“…The early vision for Microsoft's Holoportation TM communication technology was to increase access to specialised reconstructive surgical care in LMIC. Geospatial mapping -using census data and overland travel times -provided initial estimates for increasing timely access to specialised reconstructive care by 5 million people 2 .…”
Section: Increasing Access To Care In Lower To Middle Income Countriesmentioning
confidence: 99%
“…For example in burns, superior outcomes have been consistently found in burns centers rather than in peripheral hospitals 24 . We have previously proposed a mixed model approach incorporating decentralization of complex care services, but leveraging eHealth solutions such as 3D telemedicine, that may mitigate the need for specialist centres by providing direct round-the-clock access to specialist expertise 2 Telehealth oversight from the National Reconstructive Plastic Surgery and Burns Centre, Accra, may consequently enhance quality of local reconstructive care through skills transfer, capacity building, expedite urgent transfers, and incentivize patient healthcare utilization. Our previous research quantified inequitable access to care by utilising geospatial mapping created for the Malaria Atlas Project, using data sources provided by Open Street Map and Google that allow travel times to be quantified at a spatial resolution of 1 × 1 km 25 By extending specialist reconstructive care coverage through 3D Telemedicine to 8 district hospitals in rural Ghana, we illustrated the potential to increase population coverage within 1-hour travel time from 29.9% to 45.3% -equivalent to an additional 5.1 million people coverage 2 .…”
Section: Health Framework and Increasing Access To Carementioning
confidence: 99%
See 1 more Smart Citation